Mobile Banking in India: A Customer Experience Perspective - U, Dr.UMESH; DAS, SUBRATA; AGARWAL, Dr.RAJIV KUMAR; DAS, GOURAB; DHINAKARAN, Dr.D.PAUL; VIJAI, Dr.C. (The journal of contemporary issues in business and government, 2021)
Mobile banking has become the buzz word in the banking industry. The study has been conducted the customers Opinion towards Mobile banking. A self-administrated questionnaire had been developed and distributed among the respondents. Out of the 350 questionnaires, only 267 useable questionnaires were returned. The collected data have tested with SPSS. Demographic profiles and awareness about mobile banking, time taken, Trust, Convenience, ease to use, security and Advantage. Have been analyzed through percentage analysis and chi-square tests. Also examines customer’s awareness, mobile banking products and services, and also perception about mobile banking.